Sistem Informasi Penerima Beasiswa Kurang Mampu pada SMA Negeri 13 Banda Aceh - Akhrimullah (Jurnal Sistem Komputer (SISKOM), 2021)
The Information System for Less Privileged Scholarship Recipients at SMA Negeri 13 Banda Aceh is designed to streamline and optimize the management of scholarships awarded to financially disadvantaged students. This system offers a comprehensive platform for both administrators and recipients, facilitating efficient communication, transparent allocation of funds, and robust monitoring of academic progress. By integrating features such as online application submission, automated eligibility assessment, and real-time notifications, the system enhances accessibility and reduces bureaucratic barriers for applicants. Administrators benefit from centralized data management, enabling them to allocate resources judiciously and track the impact of scholarships on student performance. Moreover, the system incorporates security measures to safeguard sensitive information and ensure compliance with data protection regulations. Key functionalities include financial tracking, academic performance monitoring, and reporting capabilities. Overall, the Information System for Less Privileged Scholarship Recipients at SMA Negeri 13 Banda Aceh represents a significant advancement in promoting educational equity and empowering underprivileged students to pursue academic excellence.